Giant photovoltaic effect of ferroelectric domain walls in perovskite single crystals - Inoue, Ryotaro (Sci Rep, 2015)
The photovoltaic (PV) effect in polar materials offers great potential for light-energy conversion that generates a voltage beyond the bandgap limit of present semiconductor-based solar cells. Ferroelectrics have received renewed attention because of the ability to deliver a high voltage in the presence of ferroelastic domain walls (DWs). In recent years, there has been considerable debate over the impact of the DWs on the PV effects, owing to lack of information on the bulk PV tensor of host ferroelectrics. In this article, we provide the first direct evidence of an unusually large PV response induced by ferroelastic DWs—termed ‘DW’-PV effect. The precise estimation of the bulk PV tensor in single crystals of barium titanate enables us to quantify the giant PV effect driven by 90° DWs. We show that the DW-PV effect arises from an effective electric field consisting of a potential step and a local PV component in the 90° DW region. This work offers a starting point for further investigation into the DW-PV effect of alternative systems and opens a reliable route for enhancing the PV properties in ferroelectrics based on the engineering of domain structures in either bulk or thin-film form.